Engaging students as co‐creators of course resources and learning experiences. (19th September 2021) - Carle, Myriam S.; Deng, Jacky M.; Huang, Denzel; Lapierre, Keith R.; Mesnic, Natalie; Bodé, Nicholas E.; Featherstone, Ryan B.; Ingram, Quinn; O'Connor, Emily K.; Roberge, Sebastien; Roy, Kevin; Veilleux‐Deschênes, Joëlle; et al.
Abstract: This article focuses on the benefits and barriers to engaging students as partners in educational projects.